STAGES OF TEACHING SCHOOLCHILDREN THE HISTORY OF THE ORIGIN OF DRAWING (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article covers the pedagogical stages of teaching schoolchildren the history of the emergence and development of drawing. The development of drawing from ancient civilizations to modern technologies is analyzed. The importance of the historical approach in the formation of spatial imagination, technical thinking and graphic literacy in students is substantiated. The methodology for using historical materials in teaching drawing and their impact on educational effectiveness is also revealed.